PENGARUH BOKASHI TERHADAP PRODUKSI PADI (Oryza sativa L.) - Ahmad Raksun (Postgraduate, University of Mataram, 2018)
This research has done in Ketangga Jeraeng Village East Lombok. The objective of this research are: (1) to know the effect of bokashi on the production of rice (2) to identify the dosage of bokashi in order that rice can product optimally. Complately randomized design with four replicates were used in this research. Data analysis with Anova and least significant different (LSD).The result of this research are: (1) the application of bokashi has significant effect on the production of rice, (2) the dosage of bokasi that must be given in order that rice can product optimally is 0,8 kg bokashi/10 kg soil.Keywords: Bokashi, Production, Rice